Genetic deletion of neuronal PPARγ enhances the emotional response to acute stress and exacerbates anxiety: an effect reversed by rescue of amygdala PPARγ function - Domi, Esi; Spanagel, Rainer (The journal of neuroscience, 2016)
PPARγ is one of the three isoforms of the Peroxisome Proliferator-Activated Receptors (PPARs). PPARγ is activated by thiazolidinediones such as pioglitazone and is targeted to treat insulin resistance. PPARγ is densely expressed in brain areas involved in regulation of motivational and emotional processes. Here, we investigated the role of PPARγ in the brain and explored its role in anxiety and stress responses in mice. The results show that stimulation of PPARγ by pioglitazone did not affect basal anxiety, but fully prevented the anxiogenic effect of acute stress. Using mice with genetic ablation of neuronal PPARγ (PPARγNestinCre), we demonstrated that a lack of receptors, specifically in neurons, exacerbated basal anxiety and enhanced stress sensitivity. The administration of GW9662, a selective PPARγ antagonist, elicited a marked anxiogenic response in PPARγ wild-type (WT), but not in PPARγNestinCre knock-out (KO) mice. Using c-Fos immunohistochemistry, we observed that acute stress exposure resulted in a different pattern of neuronal activation in the amygdala (AMY) and the hippocampus (HIPP) of PPARγNestinCre KO mice compared with WT mice. No differences were found between WT and KO mice in hypothalamic regions responsible for hormonal response to stress or in blood corticosterone levels. Microinjection of pioglitazone into the AMY, but not into the HIPP, abolished the anxiogenic response elicited by acute stress. Results also showed that, in both regions, PPARγ colocalizes with GABAergic cells. These findings demonstrate that neuronal PPARγ is involved the regulation of the stress response and that the AMY is a key substrate for the anxiolytic effect of PPARγ. SIGNIFICANCE STATEMENT Peroxisome Proliferator-Activated Receptor Gamma (PPARγ) is a classical target for antidiabetic therapies with thiazolidinedione compounds. PPARγ agonists such as rosiglitazone and pioglitazone are in clinical use for the treatment of insulin resistance. PPARγ has recently attracted attention for its involvement in the regulation of CNS immune response and functions. Here, we demonstrate that neuronal PPARγ activation prevented the negative emotional effects of stress and exerted anxiolytic actions without influencing hypothalamic-pituitary-adrenal axis function. Conversely, pharmacological blockade or genetic deletion of PPARγ enhanced anxiogenic responses and increased vulnerability to stress. These effects appear to be controlled by PPARγ neuronal-mediated mechanisms in the amygdala.